2023
DOI: 10.1021/acs.chemmater.2c03574
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoelastic Coupling and Cryogenic Magnetocaloric Effect in Two-Site Disordered GdSrCoFeO6 Double Perovskite

Abstract: The development of new magnetic refrigerants demands an effective investigation of materials with a large magnetocaloric effect in a wide temperature range. Herein, we report on the structural, magnetic, and magnetocaloric properties of the two-site disordered double perovskite GdSrCoFeO 6 prepared by the modified solid-state synthesis method. Temperature-dependent synchrotron X-ray diffraction analysis revealed that GdSrCoFeO 6 crystallizes in the orthorhombic phase (Pnma), with Gd 3+ /Sr 2+ and Co 2+/3+ /Fe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 117 publications
4
19
0
Order By: Relevance
“…The temperature evolution of these parameters is shown in figure 4(c). The change in the lattice parameters at the magnetic ordering is referred as magnetoelastic coupling and reported in many other systems also [38,39]. This supports the correlation between structural and magnetic properties and magnetoelastic coupling in the studied sample.…”
Section: Mn 190 Cr 010 O 3 (Mco)supporting
confidence: 86%
“…The temperature evolution of these parameters is shown in figure 4(c). The change in the lattice parameters at the magnetic ordering is referred as magnetoelastic coupling and reported in many other systems also [38,39]. This supports the correlation between structural and magnetic properties and magnetoelastic coupling in the studied sample.…”
Section: Mn 190 Cr 010 O 3 (Mco)supporting
confidence: 86%
“…On the other hand, even if the Ho ion has a greater J = 8 ( S = 2 and L = 6), the corresponding MOF only yields a −Δ S M max of 3.71 J/kg·K at 17 K. Thus, from the magnetization point of view, we observed that PM moment and M S play an important role in enhancing the magnetic entropy change values in the α-RPF-4 series. Also, as the magnetoelastic effect is the result of a strong interaction between the lattice and the magnetic interactions, the magnetic entropy change is associated with the short-range magnetic interaction of ions in the system, which is intensified by changes in bond length and the lattice reorganization upon cooling …”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, these n values depend on the magnetic transition temperature and the critical exponents of each compound, although further studies would be needed in this regard. From the −Δ S M ( T ) curves, we have calculated the relative cooling power (RCP) expressed as RCP = |Δ S M max | × δ T fwhm (δ T fwhm is full width at half-maximum) . The δ T fwhm was obtained for the maximum curves at Δ H = 0–7 T through Lorentzian adjustments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations